e-EduTour : The Digital International Student Mobility Project - Nur Khairunnisa, Rethinasamy; Wee, Zulaica Wan Ling; Wong, Esther Hau Si; Marcella Wee, Wilbur; Soubakeavathi, Rethinasamy (AMCS PRESS, 2022)
International student mobility programs play an important role in fostering a holistic development of university students. In an effort to ensure its continuity despite the travel restrictions due to the COVID-19 pandemic, a team of Universiti Malaysia Sarawak (UNIMAS) undergraduates embarked on an initiative to create a digital version of student mobility with the guidance from their supervisor. The project named e-EduTour includes introduction to UNIMAS campus, tour of tourist attractions, taste of local food, exposure to local culture, and English language lessons. The project was successfully commercialized to Japanese partner university students. This paper provides an illustrative case study of the journey undertaken by the host university undergraduates in creating the e-EduTour, examine the foreign participants’ views about the e-EduTour’s components and university student buddies’ opinion about their experience. The data gathered via questionnaire from the Japanese participants showed that they view the e-EduTour content as very good and especially value the support given by the student buddies. The data gather from reflections of the UNIMAS team show that working on the e-EduTour project provided an opportunity for them to apply knowledge learnt in classroom to solve a real-life problem by collaborating with peers from various disciplines of study, learn through experience in a fun and exciting way, form friendship with foreign students, as well as foster personal growth. The findings clearly indicate that the digital version of short-term student mobility is possible and could enrich both the host buddies as well as the foreign participants’ learning, despite the physical distance.